Analysis of Groundwater Pollution from an Unlined Constructed Wetland Sludge Drying Bed - Adeniran, A. E.; Ajibola, O. I.; Aina, A. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Sludge drying beds (SBDs) are part of wastewater treatment processes where dewatering and reduction of water content from the substrate sludge take place to enhance caking and thus facilitate handling and disposal. In this study, the effect of the operation of an unlined drying bed of a constructed wetland for domestic wastewater treatment on the adjourning groundwater was investigated. Experimental boreholes for water quality monitoring were constructed downstream of the SBD prior to its operation. Preliminary investigations of the quality of water in the boreholes were carried out before the operation of the SBD. The concentration levels of pH, Conductivity, Total Dissolved Solids, Colour, Mn, Fe, SO4, NO3, Total Coliform and e-coli were used to empirically and statistically determine the level of pollution of the ground water during the operation of the SDB. The 2-way ANOVA at (=0.05) showed that the operation of the SBD had statistically significant impact on the quality of the groundwater on all the observed parameters. For the parameters observed, p<0.05 (p=0.00 for the averages of pH, EC, TDS, Turbidity, Colour, Mn+2, Fe+2, SO4 and NO3), while p=0.0028 and 0.0018 for the averages of Total coliform and E.coli respectively in all the boreholes. The distances from the discharge point of the SDB were at 15m, 20m, 25m, 30m, 35m, 40m and 50m for boreholes 1, 2, 3, 4, 5, 6 and 7 respectively. Also, comparison of the means of the quality parameters with the allowable limits set by the Nigerian National Environmental Surface and Groundwater Quality Control Regulations (NSGQCR) indicated that the operation of the SBD rendered the quality of the groundwater unacceptable.